OAK EXTRACT RECEIVING AND USING FOR AGING ACCELERATION OF BRANDY ALCOHOL (World Bulletin of Social Sciences, 2022)
The article "Receiving and using oak extract for accelerated aging of brandy alcohol" investigates the chemical composition of oak wood. Oak wood is known to be rich in phenolic compounds, lignins, the decomposition and oxidation products of which enrich brandy alcohol with biologically active compounds that add to its smoothness and velvetiness. The article examines the chemical compounds in oak barrel trunks. Oak extract was obtained through experimental studies . Technological modes of obtaining oak extract were established :. Quality of oak shredding; Extractors for processing oak wood cells, washing and drying conditions of oak were selected; Oak processing temperature regimes. The blend of 2-year-old brandy alcohol obtained with m 's extract was equated to the 3-year-old brand in terms of chemical composition and tasting data.